Experience of Kangaroo Mother Care (KMC) at Children Hospital Chandka Medical College (SMBB Medical University Larkana (Medical Forum Monthly, 2022)
Objective: To determine the effectiveness of kangaroo mother care in low birth weight infants at Larkana Children's Hospital.Study Design: Descriptive, cross-sectional studyPlace and Duration of Study: This study was conducted at the Kangaroo mother care unit, Children hospital CMC Larkana from 01.08.2021 to 25.02.2022.Materials and Methods: Total of 490 newborns were included in the study, mostly of infants were registered in first week of life, participation of male 55% is more than female 45%. According to gestational age 56% infants were term and 40 percent were preterm, while 54% were below 1500g and 29% below 2000gms. All infants were on exclusive breast feeding.Results: Average days required to start weight gain were 3.2 days Average weight gain per day were 33.4 grams per day. Average stay in KMC ward was 7.1 days.Conclusion: KMC is a low-cost, safe strategy that has been demonstrated to reduce the length of stay in the hospital for preterm and/or low-birth-weight infants.